SufT is required for growth of Mycobacterium smegmatis under iron limiting conditions. Issue 3 (20th December 2019) - Tamuhla, Tsaone; Joubert, Lydia; Willemse, Danicke; Williams, Monique J.
Abstract : Iron-sulphur (FeS) clusters are versatile cofactors required for a range of biological processes within cells. Due to the reactive nature of the constituent molecules, assembly and delivery of these cofactors requires a multi-protein machinery in vivo . In prokaryotes, SufT homologues are proposed to function in the maturation and transfer of FeS clusters to apo-proteins. This study used targeted gene deletion to investigate the role of SufT in the physiology of mycobacteria, using Mycobacterium smegmatis as a model organism. Deletion of the sufT gene in M. smegmatis had no impact on growth under standard culture conditions and did not significantly alter activity of the FeS cluster dependent enzymes succinate dehydrogenase (SDH) and aconitase (ACN). Furthermore, the Δ sufT mutant was no more sensitive than the wild-type strain to the redox cycler 2, 3-dimethoxy-1, 4-naphthoquinone (DMNQ), or the anti-tuberculosis drugs isoniazid, clofazimine or rifampicin. In contrast, the Δ sufT mutant displayed a growth defect under iron limiting conditions, and an increased requirement for iron during biofilm formation. This data suggests that SufT is an accessory factor in FeS cluster biogenesis in mycobacteria which is required under conditions of iron limitation.